Time-resolved structural dynamics of thin metal films heated with femtosecond optical pulses - Chen, Jie (National Academy of Sciences, 2011)
We utilize 100 fs optical pulses to induce ultrafast disorder of 35- to 150-nm thick single Au(111) crystals and observe the subsequent structural evolution using 0.6-ps, 8.04-keV X-ray pulses. Monitoring the picosecond time-dependent modulation of the X-ray diffraction intensity, width, and shift, we have measured directly electron/phonon coupling, phonon/lattice interaction, and a histogram of the lattice disorder evolution, such as lattice breath due to a pressure wave propagating at sonic velocity, lattice melting, and recrystallization, including mosaic formation. Results of theoretical simulations agree and support the experimental data of the lattice/liquid phase transition process. These time-resolved X-ray diffraction data provide a detailed description of all the significant processes induced by ultrafast laser pulses impinging on thin metallic single crystals.